2022
DOI: 10.1108/ijchm-12-2021-1515
|View full text |Cite
|
Sign up to set email alerts
|

Two decades of research on halal hospitality and tourism: a review and research agenda

Abstract: Purpose This study aims to conduct a synopsis and overview of past research that discussed halal hospitality development and the halal travel market. Design/methodology/approach An extensive systematic review of 108 articles within the hospitality and tourism domain from 2000 to 2021 that were extracted from the Web of Science and Scopus databases was exhaustively assessed. Findings The results are visualised to determine the most thematic domains, contexts and concepts previously discussed. It also comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 121 publications
0
12
0
Order By: Relevance
“…Similarly, despite some focus on topics such as food safety (MacLaurin, 2001; Tarulevicz and Ooi, 2021), healthy eating (Al-Ansi et al , 2022; Jeong et al , 2019), hotel cleanliness (Zemke et al , 2015) and hotel safety during COVID-19 (Choi et al , 2022; Morosan and DeFranco, 2021), no hospitality studies appear to have addressed travel medicine thus far. Only a handful of papers in travel medicine journals have mentioned hotel guests’ health; most have covered food and waterborne infectious diseases such as diarrhea, norovirus, malaria, Legionnaires’ disease and COVID-19 (Erdogan and Arslan, 2007; Leshem et al , 2016; Fan et al , 2021); however, as confirmed by the pandemic’s devastating blow to tourism and hospitality, safety and health are of paramount importance in consumer-centered sectors (Wilks and Oldenburg, 1995; Maher et al , 2022).…”
Section: Travel Medicinementioning
confidence: 99%
“…Similarly, despite some focus on topics such as food safety (MacLaurin, 2001; Tarulevicz and Ooi, 2021), healthy eating (Al-Ansi et al , 2022; Jeong et al , 2019), hotel cleanliness (Zemke et al , 2015) and hotel safety during COVID-19 (Choi et al , 2022; Morosan and DeFranco, 2021), no hospitality studies appear to have addressed travel medicine thus far. Only a handful of papers in travel medicine journals have mentioned hotel guests’ health; most have covered food and waterborne infectious diseases such as diarrhea, norovirus, malaria, Legionnaires’ disease and COVID-19 (Erdogan and Arslan, 2007; Leshem et al , 2016; Fan et al , 2021); however, as confirmed by the pandemic’s devastating blow to tourism and hospitality, safety and health are of paramount importance in consumer-centered sectors (Wilks and Oldenburg, 1995; Maher et al , 2022).…”
Section: Travel Medicinementioning
confidence: 99%
“…For example, in Malaysia, an interesting result was found by Rahman and Zailani (2017) that only 17 hospitals out of 61 involved in medical tourism implemented Islamic practices in these hospitals. However, the authors emphasize that Malaysian medical tourism providers do not apply various Muslim-friendly services due to the absence of Islamic medical tourism standards (Al-Ansi, Olya & Han, 2022). In this regard, based on the increase in Islamic friendly hospitals, the question raised here is whether an international Islamic accreditation body is needed to assess medical tourism providers, which in turn guarantees the satisfaction of Muslim medical tourists (Al-Ansi, Olya & Han, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing number of Muslim medical tourists, especially from North Africa and the Middle East who are highly Muslim, makes many destinations to consider it as a market segment that must be targeted (Rahman & Zailani, 2017). Malaysia as a medical tourism center mainly focuses on medical tourists from Muslim countries, especially from Indonesia and the Middle East, emphasizing its Islamic credentials including the availability of various facilities for Islamic practice (Al-Ansi, Olya & Han, 2022). In addition, Muslim medical tourists prefer to travel to Malaysia where Islamic hospitality is offered, including the availability of halal food and products (Rahman, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Halal tourism refers to actions or objects (e.g. hospitality, social recreational services, food, leisure, food and dress code) in tourism industry, which are permitted, acceptable and allowed in Islamic Sharia law (Al-Ansi et al, 2023;Akhtar et al, 2020). Besides, Ekka (2023) and Wibawa et al (2021) define halal tourism as subcategory of religious tourism, where visitors go for religious motives or for products such as architecture, traditions, art and culture.…”
Section: Introductionmentioning
confidence: 99%